Instabilities of Flows: With and Without Heat Transfer and Chemical Reaction - Sengupta, Tapan K.; Poinsot, Thierry; SpringerLink (Online service) (Vienna : Springer Vienna, 2010)
The articles in the book treat flow instability and transition starting with classical material dealt with in an innovative and rigorous way, some newer physical mechanisms explained for the first time and finally with the very complex topic of bombustion and two-phase flow instabilities.
General Introduction on Instability and Transition -- Instability and Transition in Fluid Mechanics -- Bypass Transition -- Spatio-Temporal Instability and Transition -- Landau Equation and Multiple Hopf-Bifurcation -- Stability of Mixed Convection Boundary Layer -- Combustion and CFD for Combustion -- Waves in Reacting Flows -- Large Eddy Simulation of Real Combustors -- Two-Phase Flow Combustion -- The Growth of Rounding Errors in LES.
Keywords: Engineering; Hydraulic engineering; Engineering; Engineering Fluid Dynamics; Automotive Engineering; Fluid- and Aerodynamics